On the effects of economic fluctuations on productivity growth - Menezes, António Gomes de (2004)
We analyze the productivity effects of shocks to the real interest rate and to demand and supply conditions in a world where productivity enhancing activities are disruptive. The model predicts that temporary demand downturns may have positive productivity effects if the real interest rate is not too countercyclical, and that supply shocks do not affect productivity growth. The model is used to derive refined novel empirical tests on the so-called Opportunity Cost View of recessions (Aghion and Saint-Paul (1998)) vis a vis the competing theories of learning-by-doing and capital market imperfections.